Counterintelligence in Legal Perspective: Balancing National Security and Human Rights in Indonesia - Riyanta, Stanislaus (KRTHA BHAYANGKARA, 2025)
This study examines the crucial role of counterintelligence within the legal framework of Indonesia, focusing on the inherent tension between safeguarding national security and upholding human rights in the face of evolving contemporary threats. Utilizing a qualitative legal analysis approach, this research scrutinizes existing Indonesian laws, particularly the State Intelligence Law (Law No. 17/2011), to identify their adequacy, ambiguities, and potential for legal and ethical challenges in counterintelligence operations. It analyzes how core counterintelligence functions—such as intelligence gathering, surveillance, and neutralization—are regulated and the extent to which they align with international human rights standards. The study highlights critical legal gaps concerning privacy protection, accountability mechanisms, and oversight of intelligence agencies. Based on this analysis, it proposes concrete legal reforms and policy recommendations aimed at strengthening Indonesia's counterintelligence capabilities while ensuring robust adherence to democratic principles, rule of law, and fundamental human rights. This includes advocating for clearer legal mandates, enhanced independent oversight, and transparent accountability frameworks to foster public trust and legitimacy in counterintelligence practices.